2016
DOI: 10.1128/iai.01001-15
|View full text |Cite
|
Sign up to set email alerts
|

Flagellar Cap Protein FliD Mediates Adherence of Atypical Enteropathogenic Escherichia coli to Enterocyte Microvilli

Abstract: The expression of flagella correlates with different aspects of bacterial pathogenicity, ranging from adherence to host cells to activation of inflammatory responses by the innate immune system. In the present study, we investigated the role of flagella in the adherence of an atypical enteropathogenic Escherichia coli (aEPEC) strain (serotype O51:H40) to human enterocytes. Accordingly, isogenic mutants deficient in flagellin (FliC), the flagellar structural subunit; the flagellar cap protein (FliD); or the Mot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…The H type of E. coli refers to the flagellin component of the flagella (55). The presence of flagellin is important for adherence and stimulation of cytokines by aEPEC in in vitro studies (56)(57)(58), and mutations in the fliC gene of O113:H21 Shiga-toxin producing E. coli lead to a decreased association with the colonic epithelium in experimentally infected mice (59). However, in that study, it is unclear if the impaired epithelial association in the mutated H21 was specific to that H type (H21).…”
Section: Discussionmentioning
confidence: 99%
“…The H type of E. coli refers to the flagellin component of the flagella (55). The presence of flagellin is important for adherence and stimulation of cytokines by aEPEC in in vitro studies (56)(57)(58), and mutations in the fliC gene of O113:H21 Shiga-toxin producing E. coli lead to a decreased association with the colonic epithelium in experimentally infected mice (59). However, in that study, it is unclear if the impaired epithelial association in the mutated H21 was specific to that H type (H21).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it has been recently shown that the flagellar cap protein FliD of an aEPEC strain (serotype O51:H40) binds to unknown receptors on intestinal Caco-2 cell microvilli 92 . Interestingly, an anti-FliD serum and purified FliD reduced adherence of the aEPEC as well as that of tEPEC, EHEC and ETEC prototype strains to the same cell line 92 .…”
Section: Typical and Atypical Enteropathogenic E Colimentioning
confidence: 99%
“…Interestingly, an anti-FliD serum and purified FliD reduced adherence of the aEPEC as well as that of tEPEC, EHEC and ETEC prototype strains to the same cell line 92 . Furthermore, it has been suggested that adherence of aEPEC of serotype O26:H11 may be mediated by binding of the flagellin protein FliC (the subunit of the flagella shaft) to cellular fibronectin 93 .…”
Section: Typical and Atypical Enteropathogenic E Colimentioning
confidence: 99%
“…Chemotaxis and motility by flagella are pathogenic attributes that contribute to biofilm formation, adherence, and invasion in several pathogens; in addition, flagella stimulate the secretion of effector molecules and modulation of the immune system [18][19][20]. Flagellar motility plays an important role in the pathogenesis of Helicobacter pylori, Pseudomonas aeruginosa, Vibrio cholerae, Salmonella species, and E. coli [18,[21][22]. The main advantage of bacterial flagella is the ability to direct bacterial movement to a specific colonization site in the host [23].…”
Section: Discussionmentioning
confidence: 99%